Especiação redox de crômio em amostras de solos contaminados - Canevari, Natália Tostes (Universidade Federal de São Carlos, 2012)
Chromium and its compounds are employed in various industrial processes, and these activities are responsible for the disposal of significant amounts of materials containing this element in the environment. Due to the known toxic feature of Cr(VI) in biological systems, the determination of chromium species has acquired great importance in environmental chemistry. In this study three analytical strategies were combined, X-ray absorption spectroscopy, flame atomic absorption spectrometry and UV-Vis molecular absorption spectrophotometry, in order to identify and determine Cr(III) and (VI) in contaminated soil samples. The samples were collected around the Comandante Ferraz Antarctic Station, a Brazilian scientific station in Antarctica. For the pseudototal chromium analysis, acid digestion was employed for sample preparation and determinations were performed using a flame atomic absorption spectrometer. Na2CO3 0.28 mol L-1 - NaOH 0.5 mol L-1 extractor solution and heating were used for Cr(VI) extraction in the samples, and preliminary identification of this specie was performed using XANES and EXAFS techniques at the Brazilian Synchrotron Light Laboratory. For Cr(VI) determination, NaOH 0.1 mol L-1 and heating were employed for the extraction of the specie, and determinations were based on the reaction of Cr(VI) with the colorimetric reagent diphenylcarbazide in acid medium, using a flow injection analysis system coupled to a molecular absorption spectrophotometer. The quantification of Cr(III) was carried out by subtraction between the pseudototal chromium concentration and Cr(VI) concentration. Results obtained were compared with those calculated from the determination of Cr(VI) with diphenylcarbazide in batch mode. Chromium (VI) concentrations determined in soil samples using both methods were discordant, and these differences were originated from problems occurred in the developed flow injection analysis system.
Redox especiation of chromium in contaminated soil samples
Keywords: Química analítica; Especiação química redox; Solos; Espectrofotometria; Análise por injeção de fluxo; Espectroscopia de absorção de raios X; CIENCIAS EXATAS E DA TERRA::QUIMICA